The Effect of the Mineral Content of the Leg-Horn and the Age of Sheep on the Mechanical Parameters of the Horn - Szórádi, Tibor (Acta Agraria Debreceniensis, 2003)
Species and individual animals with hard leg-horn have higher resistance against foot diseases. The reason for this is the fact, that bacteria can penetrate the hard leg-horn with more difficulty than the soft leg-horn, and in this way it is also more difficult for them to cause an illness. From among the mechanical parameters of the leg-horn the P = 0.1% negative linear correlation between the hardness and the water contents of the horn is significant. There is a positive linear correlation between the shock resistance and the water contents of the leg-horn. In the case of air-dry horn (with less than 8% water contents) there is a positive linear correlation between the Ca- and Zn contents as well as the Ca:P ratio and the hardness of the horn. The results suggest that the wider the Ca:P ratio of the horn, the harder the horn is, while the water content is the same. The leg-horn of the Hungarian Merino ewes have larger Ca contents and wider Ca:P ratio than juvenile animals have. This is why the juvenile animals with a softer leg-horn can be more susceptive to foot diseases than the older animals.